Lactate levels and hormonal responses to excessive training in elite swimmers - Oh, J. K.; Yoo, R. R.; Cho, J. Y.; Cho, Y. E. (Medicine & Science in Sports & Exercise, 1998)
Mature elite swimmers were monitored through 10 weeks of training for immunoglobulin and hormonal changes. The stages of training were normal training for weeks 1-5 (5 x 6,000 m), week 6 reduced work, and weeks 7-10 100% increased work (5 x 12,000 m). Measures were taken at the end of weeks 5 and 10. Excessive training produced increased lactate levels and different plasma catecholamine concentrations. No differences between different workload phases were observed in cortisol levels. Plasma insulin levels were lower in the overtraining period (insulin helps released glucose enter cells where it can be used for energy). Implication: Plasma insulin levels and lactate levels after standardized work bouts might have the potential to be indexes of overtraining.